Voyage à huis clos - Caroline Antoine (Viatica)
Fueled by the scholarly expeditions of the eighteenth and nineteenth centuries, natural history cabinets have close ties with travel. This article examines the different aspects of this relationship by taking the example of Jean-Baptiste d’Allard. Over the years, his cabinet became the nucleus of a vast network of exchanges that allowed him to purchase numerous exotic specimens. The galleries of his collection offer a stroll among these objects evocative of distant and often mysterious lands. The practice of travelling behind closed doors was not considered paradoxical in the nineteenth century. On the contrary, it proved to be a complementary step, even necessary to undertake an enlightened journey.